S41 Tracheostomy ventilation in motor neurone disease: a multi-centre review. (15th November 2017) - Palmer, JM; Armstrong, AD; Kathiresan, B; Latham, MJ; Moses, R
Abstract : Introduction and Objectives: Little data exists regarding use of tracheostomy ventilation (TV) in patients with motor neurone disease (PwMND). NICE 2016 does not provide guidance for use of TV. Some centres offer TV as a treatment option. Data suggest TV in PwMND can prolong life and is more readily accepted by young males. It is hypothesised that starting TV in PwMND is intrusive to quality of life and leads to unacceptably, long hospital stays. Methods: 4 HMV centres obtained data by retrospective case-note review of patients set-up on TV as a consequence of MND between January 1998 and December 2016. Results: 38 patients (26 male) were included. Average age at tracheostomy was 59.3 (range 26–78). 79% (n=30) of patients had emergency tracheostomy v 21% elective. 76% (n=23) of emergencies were related to acute illness requiring intubation. 75% (n=6) of those who elected for TV wanted to live as long as possible or were struggling with continuous use of non-invasive interfaces, all of these lived with a partner or parent. 41% were managed on respiratory wards for the majority of the inpatient stay. After commencing TV, mean length of stay was 7 weeks for those admitted electively v 18 weeks as an emergency. 2 patients died in hospital. 71% were discharged to their own home. Majority of home care was undertaken by skilled carers (22 hrs/day) rather than Registered Professional (1.8 hrs/day). 3 patients were weaned, 1 successfully. Mean length of life post TV was 3.7 years (range 0–15 years), with longer life expectancy in the elective group (5.1 years). A total of 52% patients died during the timeframe. 45% of deaths were unexpected the rest expected or planned withdrawal. Conclusion: TV in PwMND could be associated with increased length of life. In keeping with published data there appears to be a high incidence of unexpected death. PwMND and TV tend to be discharged to their own home with skilled carers. Length of hospital stay for planned admission is not long as is anecdotally suggested. Further work, including detailed nationwide audit, national ventilation registry and national guidance may be helpful.